IMPACT OF LIQUIDITY MANAGEMENT ON PROFITABILITY OF INDIAN PUBLIC SECTOR BANKS: A COMPARATIVE STUDY - Yadav, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The examination of prominent public sector banks in India from 2019-20 to 2023-24 revealed significant trends and discoveries, providing critical insights into their financial health and performance. The research concentrated on five leading banks: Bank of India (BOI), State Bank of India (SBI), Punjab National Bank (PNB), Bank of Baroda (BOB), & Industrial Development Bank of India (IDBI). The profitability ratios, comprising Net Profit Ratio, Operating Profit Ratio (OPR), Return on Net Worth (RONW), Return on Capital Employed (ROCE), Book Value per Share, and Earnings Per Share (EPS), demonstrated varying trends among the banks. Although SBI and BOB consistently exhibited favorable ratios, BOI and IDBI encountered difficulties, incurring losses and demonstrating inefficiencies in capital deployment. The discrepancies in these statistics underscored the divergent financial fortunes of the banks. Liquidity parameters, including the Current Ratio & Quick Ratio, exhibited steady positions for SBI & PNB, while others displayed variable movements. IDBI continuously maintained a superior Current Ratio, signifying a robust liquidity position. Nonetheless, the distinct liquidity ratios exerted differing levels of impact, underscoring the necessity of a comprehensive strategy for liquidity management. Dividend payout ratios vary, indicating each bank's own strategy for dividend distribution. SBI regularly exhibited a large Dividend Payout Ratio, signifying a propensity to issue dividends, whilst BOI and IDBI maintained lower average percentages. Friedman tests indicated considerable disparities in financial ratios across the chosen banks, highlighting the necessity for a detailed understanding of each bank's plans and performances. The report offers a thorough analysis of the financial environment of prominent public sector banks. The findings underscore the necessity of evaluating many financial metrics for a comprehensive assessment of a bank's financial well-being. The banks' divergent performances highlight the dynamic characteristics of the banking system, prompting policymakers and stakeholders to modify policies in response to the unique difficulties and possibilities encountered by each institution.